The development and application of spatial information systems for environmental science - Hallett, Stephen H. (Cranfield University, 1998)
This thesis shows how advances in IT allow the development of Environmental Information System (EIS) applications contributing to the advancement of environmental science and management. The research presented elucidates and evaluates the applications for EIS within the environmental and natural resource sciences with specific reference to soils. In supporting environmental suitability and risk assessment, the following research objectives were met: 1. Derive and construct new datasets, facilitating the development of EIS applications 2. Using these and other datasets, develop and demonstrate the validity of specific spatial EIS applications within the context of sustainable soil resource management 3. Evaluate, develop and apply emergent technological principles such as the objectoriented paradigm to the development of such EIS applications The research shows that the EIS approach offers environmental researchers and practitioners powerful tools to facilitate the collection and preparation, representation, structure and management, manipulation and presentation of environmental data. Such data can be used to aid disciplinary and interdisciplinary scientific research, such as risk modelling, data quality control and longitudinal studies. Through the interaction of multi-disciplinary datasets and models, the EIS contributes to the development of a holistic, interdisciplinary understanding of pertinent and contemporary environmental issues. EIS applications are constrained by the availability and affordability of technology, as well as by the quality of the data, models and scientific research they are based upon. With the constantly improving capabilities and cost-performance of IT there should be a continual review of methodologies to maximise usage of available technology. A well-developed synergy between environmental science and IT is important and automatic adoption of the most recently emergent information technologies is not always to be recommended for EIS development. The choice of software tools utilised in EIS development must be based upon the requirements for integration with existing systems, reliability, adherence to industry standards, expenditure, staff training needs, experimentation and efficiency. The incorporation of a spatial element within the decision-making process extends a powerful visual dimension to the traditional approaches used to portray environmental systems. The research identifies the emergent 'object paradigm' as significant for EIS development, being effective for describing complex spatial environmental phenomena. An object-oriented approach facilitates the presentation of abstracted, packaged scientific information in a directly accessible form. The EIS offers a powerful strategic tool for supporting decision-making in environmental management. The EIS applications presented supported Soil Quality and Protection, Pollution Control and Impact Assessment, Water Resource and Catchment Management, Soil and Land Management and Environmental Risk Assessment.